Hukum sebagai Instrumen Rekayasa Sosial dalam Pembentukan Legal consciousness melalui Penerapan ETLE - Putri Wahyu Widayanti (Yayasan Penelitian Dan Pengabdian Masyarakat Sisi Indonesia, 2026)
From a sociology of law perspective, law is not merely understood as a body of written norms, but also as an instrument of social engineering that directs behavioral change within society. This article examines the implementation of Electronic Traffic Law Enforcement (ETLE) in Indonesia as a manifestation of law as social engineering in shaping public legal consciousness toward traffic safety. This study adopts a qualitative approach using a juridical-sociological method through the analysis of legislation, academic literature, and socio-legal theoretical frameworks. The analytical framework is based on Roscoe Pound’s theory of law as a tool of social engineering, Lawrence M. Friedman’s legal system theory, the concept of legal consciousness developed by Ewick and Silbey, and Talcott Parsons’ structural-functional theory through the AGIL scheme. The findings demonstrate that ETLE functions not only as a technological innovation in law enforcement but also as a mechanism of social integration that constructs new legal experiences for society. Through technology-based surveillance, ETLE encourages a shift in compliance patterns from fear-based obedience (compliance) toward the internalization of traffic safety values (internalization). However, the effectiveness of ETLE as an instrument of social engineering remains influenced by structural capacity, legal substance, and prevailing legal culture. Therefore, the success of ETLE in fostering a sustainable traffic safety culture depends on strengthening legal consciousness through synergy among legal structure, substance, and culture.